Sintering method of zinc oxide-doped high-density indium-free target material

By mixing alumina and zinc oxide powder in a specific proportion and sintering, a high-density indium-free target is prepared, which solves the problem of insufficient insulation of alumina target, and achieves the improvement of high conductivity and photoelectric properties. It is suitable for thin film deposition and optoelectronic device manufacturing.

CN119661201APending Publication Date: 2025-03-21ZHUZHOU TORCH ANTAI NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510064685.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Due to its strong insulation, existing alumina targets are difficult to improve the electrical conductivity and optical properties of the film in some applications.

Method used

High-density indium-free target material is prepared by mixing alumina and zinc oxide powder in a specific proportion and adding sintering aids.

Benefits of technology

The high density and low resistivity of the target material are achieved, and its conductivity and photoelectric properties are improved. It is suitable for thin film deposition and optoelectronic device manufacturing.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a sintering method of a zinc oxide-doped high-density indium-free target material, and relates to the technical field of target material sintering, and the sintering method comprises the following steps: uniformly mixing alumina and zinc oxide powder according to a mass ratio of (9-19): 1, and adding a sintering aid; adding deionized water and a dispersing agent, carrying out ball milling for 12-24 hours, filtering and drying to obtain primary powder; screening the first-grade powder to obtain second-grade powder of which the granularity is less than or equal to 20 microns; drying the secondary powder until moisture is completely removed, and pressing the secondary powder into a target material shape by using cold isostatic pressing or hot isostatic pressing; and sintering at 1200-1450 DEG C in an oxygen atmosphere for 2-4 hours, and cooling to room temperature after sintering, thereby obtaining the product. The target material sintered by the sintering method of the high-density indium-free target material doped with the zinc oxide has relatively high density and relatively low resistivity, the process is simple, convenient and stable, and the method can be widely applied to the fields of thin film deposition, manufacturing of optoelectronic devices and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of target material sintering, and in particular to a sintering method for a high-density indium-free target material doped with zinc oxide. Background Art

[0002] With the development of the electronics industry and optoelectronics industry, targets, as key materials for thin film deposition and optoelectronic device manufacturing, have played an important role in integrated circuit manufacturing, solar cells, displays and other fields. At present, indium targets (especially indium tin oxide targets) are gradually challenged by alternative materials due to high prices, limited resources, environmental pollution and other issues. Therefore, the demand for indium-free targets is increasing. Alumina (Al2O3) materials have gradually become an important choice to replace indium targets due to their high melting point, high strength and chemical stability. However, due to the strong insulation of aluminum oxide itself, its electrical properties need to be further improved in some applications to improve the conductivity and optical properties of the film. Therefore, the conductivity and optoelectronic properties of the target can be effectively improved by doping zinc oxide (ZnO). Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a sintering method of a high-density indium-free target material doped with zinc oxide, and the specific technical solution is as follows:

[0004] A sintering method for a high-density indium-free target material doped with zinc oxide comprises the following steps:

[0005] Step 1: After mixing aluminum oxide and zinc oxide powder in a mass ratio of (9-19):1, add sintering aid;

[0006] Step 2: Add deionized water and dispersant, ball mill for 12 to 24 hours, filter and dry to obtain a primary powder;

[0007] Step 3: Screen the primary powder to obtain a secondary powder with a particle size of ≤20 μm;

[0008] Step 4: After the secondary powder is dried to completely remove moisture, it is pressed into a target shape using cold isostatic pressing or hot isostatic pressing;

[0009] Step 5: Sinter in an oxygen atmosphere at 1200-1450°C for 2-4 hours, and cool to room temperature after sintering.

[0010] Preferably, step 5 specifically includes the following sub-steps:

[0011] Step 51, preheating: heating from room temperature to 1000°C at a heating rate of 5-10°C / min;

[0012] Step 52, sintering: continue to raise the temperature to 1200-1450°C and maintain the temperature for 2-4 hours;

[0013] Step 53, cooling: cooling to room temperature at a cooling rate of 10-15°C / min.

[0014] Preferably, the sintering aid in step 1 includes calcium salt and / or borate, and the added amount thereof is 0.5% to 2% of the total mass of the aluminum oxide and zinc oxide powders.

[0015] Preferably, the dispersant in step 2 comprises citric acid or polyvinyl alcohol.

[0016] Preferably, the pressing pressure in step 4 is 50-100 MPa.

[0017] Preferably, the sintering aid is a surface-modified calcium salt-borate composite aid, and the preparation of the surface-modified calcium salt-borate composite aid comprises the following steps:

[0018] Dissolving the silane coupling agent in a solvent to prepare a modifier solution with a concentration of 0.5% to 5%;

[0019] Add calcium salt and borate to the modifier solution, stir or ultrasonicate for 1 to 3 hours, and then filter;

[0020] The modified powder was washed with deionized water and dried at 60-100°C for 2-4h;

[0021] The dried powder is sieved into a surface-modified calcium salt-borate composite additive with a particle size of ≤20 μm.

[0022] Preferably, the sintering aid is an organic polymer-modified calcium salt-borate composite aid, and the preparation of the organic polymer-modified calcium salt-borate composite aid comprises the following steps:

[0023] Dissolving an organic polymer in deionized water to prepare a polymer solution with a concentration of 2% to 10%;

[0024] Add calcium salt and borate to the polymer solution, mix thoroughly with a magnetic stirrer or ultrasonic oscillator, and then filter;

[0025] The product is obtained after drying at 60-100°C for 2-4 hours.

[0026] Preferably, the organic polymer is polyvinyl alcohol, polyacrylonitrile or polyvinyl pyrrolidone.

[0027] Preferably, the sintering method in step 5 is a gradual pressure sintering method, which specifically includes:

[0028] During preheating, the pressure gradually increases from 0.1-0.5MPa to 1-3MPa;

[0029] During sintering, the pressure gradually increases to 20-30 MPa;

[0030] During cooling, the pressure gradually decreases to 1-3 MPa.

[0031] Preferably, the sintering aid further comprises yttrium oxide and / or cerium oxide.

[0032] The target material sintered by the sintering method of the high-density indium-free target material doped with zinc oxide provided by the present invention has high density and low resistivity, and the process is simple and stable, and can be widely used in the fields of thin film deposition and optoelectronic device manufacturing. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below. The description in this part is only exemplary and explanatory and should not have any limiting effect on the protection scope of the present invention.

[0034] This embodiment provides a sintering method for a high-density indium-free target material doped with zinc oxide, comprising the following steps:

[0035] Step 1: After uniformly mixing aluminum oxide and zinc oxide powder in a mass ratio of (9-19):1, add sintering aid.

[0036] Step 2: Add deionized water and dispersant, ball mill for 12 to 24 hours, filter and dry to obtain a primary powder.

[0037] Step 3: Screen the primary powder to obtain secondary powder with a particle size of ≤20 μm.

[0038] Step 4: After the secondary powder is dried to completely remove moisture, it is pressed into a target shape using cold isostatic pressing or hot isostatic pressing.

[0039] Step 5: Sinter in an oxygen atmosphere at 1200-1450°C for 2-4 hours, and cool to room temperature after sintering.

[0040] In step 1, the mixed powder contains 90% to 95% aluminum oxide and 5% to 10% zinc oxide. Aluminum oxide mainly provides a skeleton and has good thermal stability and corrosion resistance. Doped zinc oxide can provide conductivity, photoelectric properties, etc., which can improve the electronic properties of the target material. A small amount of sintering aid can promote the sintering process of aluminum oxide and further improve the density of the target material. Aluminum oxide can be selected from high-purity aluminum oxide powder (>99.5%) with a particle size of 1 to 5 μm, and zinc oxide can be selected from high-purity zinc oxide powder (>99.9%) with a particle size of 1 to 5 μm.

[0041] In step 2, adding a dispersant and ball milling can fully disperse the powder, reduce agglomeration, and ensure the uniformity and fineness of the powder.

[0042] In step 3, the screened powder helps the subsequent sintering process and can more easily form a dense target material, improving its density and uniformity.

[0043] In step 5, high temperature sintering can promote the bonding and densification of powder particles, and finally form a target material with high density and good mechanical properties. The oxygen atmosphere helps to control the oxidation state of the surface and interior of the target material and optimize the sintering effect.

[0044] The target material sintered by the sintering method of the high-density indium-free target material doped with zinc oxide provided in this embodiment has high density and low resistivity, and the process is simple and stable, and can be widely used in the fields of thin film deposition and optoelectronic device manufacturing.

[0045] Furthermore, step 5 specifically includes the following sub-steps:

[0046] Step 51, preheating: heating from room temperature to 1000°C at a heating rate of 5-10°C / min.

[0047] Step 52, sintering: continue to raise the temperature to 1200-1450°C and maintain the temperature for 2-4 hours.

[0048] Step 53, cooling: cooling to room temperature at a cooling rate of 10-15°C / min.

[0049] Among them, preheating to 1000℃ can avoid the generation of bubbles or pores during the sintering process, and make the powder gradually adapt to the high temperature environment, while helping to reduce the generation of cracks; the sintering temperature of 1200-1450℃ helps to improve the density of the target material, while avoiding excessive oxidation or reduction reaction of the material; the cooling rate of 10-15℃ / min can avoid thermal stress caused by too rapid cooling during the cooling process or cracks caused by excessive temperature gradient, and help to improve the overall performance of the target material, especially the hardness, toughness and crack resistance of the material.

[0050] Furthermore, in step 1, the sintering aid includes calcium salt and / or borate, and the addition amount thereof is 0.5% to 2% of the total mass of the aluminum oxide and zinc oxide powders.

[0051] Among them, sintering aids can improve the sintering performance of powders, promote density improvement, reduce porosity, and enhance the mechanical properties of the final target material; calcium salts (calcium chloride, calcium nitrate or calcium oxide, etc.) can form a low-melting-point calcium-based glass phase to help powder particles combine at a lower temperature, reduce the high temperature conditions required during the sintering process, thereby reducing grain growth and controlling the grain size of the material; borates (boric acid, aluminum borates, calcium borates, etc.) help promote the dissolution-recrystallization process during sintering, and can form a low-melting-point glass phase at high temperature, which plays a role in improving the bonding of powder particles.

[0052] Furthermore, in step 2, the dispersant includes citric acid or polyvinyl alcohol.

[0053] Among them, citric acid can effectively improve the dispersibility of the powder, making the aluminum oxide and zinc oxide powders more evenly dispersed in the water, avoiding the formation of larger particles due to mutual attraction between particles; the molecular structure of polyvinyl alcohol has multiple hydrophilic groups, which can interact with water molecules and the powder surface, thereby reducing the cohesion between particles and avoiding powder agglomeration.

[0054] Furthermore, in step 4, the pressing pressure is 50-100 MPa.

[0055] Among them, the pressing pressure of 50-100 MPa can effectively reduce the porosity between powders, making the powder particles more closely arranged together, so that the powder reaches a higher density, laying a good foundation for the diffusion and bonding between powder particles during the sintering process.

[0056] Furthermore, the sintering aid is a surface-modified calcium salt-borate composite aid, and the preparation of the surface-modified calcium salt-borate composite aid comprises the following steps:

[0057] The silane coupling agent is dissolved in a solvent to prepare a modifying agent solution with a concentration of 0.5% to 5%.

[0058] Calcium salt and borate are added to the modifier solution, stirred or ultrasonicated for 1 to 3 hours, and then filtered.

[0059] The modified powder was washed with deionized water and dried at 60-100° C. for 2-4 h.

[0060] The dried powder is sieved into a surface-modified calcium salt-borate composite additive with a particle size of ≤20 μm.

[0061] Among them, the surface-modified calcium salts and borates can be more evenly distributed in the aluminum oxide and zinc oxide powders to avoid agglomeration, ensure that the powder has good density during the sintering process, and help to form a low-melting glass phase, promote the bonding between particles, so that the sintering process temperature can be lower, reducing energy consumption and sintering time; Silane coupling agents can improve the compatibility of calcium salts, borates and aluminum oxide, zinc oxide and other powders, thereby promoting particle bonding during the sintering process and improving the strength and wear resistance of the final target material.

[0062] Furthermore, the sintering aid is an organic polymer modified calcium salt-borate composite aid, and the preparation of the organic polymer modified calcium salt-borate composite aid comprises the following steps:

[0063] The organic polymer is dissolved in deionized water to prepare a polymer solution with a concentration of 2% to 10%.

[0064] The calcium salt and borate are added to the polymer solution, mixed thoroughly using a magnetic stirrer or an ultrasonic oscillator, and then filtered.

[0065] The product is obtained after drying at 60-100°C for 2-4 hours.

[0066] Among them, the addition of organic polymers can effectively improve the dispersibility of calcium salts and borates in powders, avoid agglomeration, and improve the sintering effect. It can promote the bonding between powder particles at a lower temperature, improve the sintering efficiency, make the powder more evenly bonded during the sintering process, reduce porosity, and increase the density and mechanical strength of the final target material.

[0067] Furthermore, the organic polymer is polyvinyl alcohol, polyacrylonitrile or polyvinyl pyrrolidone.

[0068] Furthermore, the sintering method in step 5 is a gradual pressure sintering method, which specifically includes:

[0069] During preheating, the pressure gradually increases from 0.1-0.5 MPa to 1-3 MPa, thereby promoting initial contact between particles and a small amount of solid phase aggregation, avoiding drastic deformation or rupture of the particles.

[0070] During sintering, the pressure gradually increases to 20-30 MPa, thereby increasing the interaction force between the particles, causing the particles to diffuse and fuse, and promoting densification during the sintering process.

[0071] During cooling, the pressure gradually decreases to 1-3 MPa, thereby avoiding uneven stress caused by thermal expansion or contraction during the cooling process, ensuring the uniformity of the material and preventing cracking or deformation.

[0072] Furthermore, the sintering aid also includes yttrium oxide and / or cerium oxide.

[0073] Among them, yttrium oxide can reduce the sintering temperature of ceramic materials and improve the fluidity of particles during the sintering process, and cerium oxide can promote the bonding and densification of particles. When yttrium oxide and cerium oxide work synergistically, they can more effectively regulate the sintering process of the material, reduce the sintering temperature, improve the bonding force of the particles, and promote the densification of the material, thereby making the performance of the final material more stable.

[0074] Specific examples are provided below. The provided examples may enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.

[0075] Embodiment 1:

[0076] Alumina powder with an average particle size of 3 μm and zinc oxide powder with an average particle size of 4 μm were selected and mixed at a mass ratio of 95:5. Then 0.5% borate was added as a sintering aid, deionized water and citric acid were used as dispersants, and wet ball milling was performed for 12 hours. The ball-milled slurry was filtered and spray-dried to obtain a dry powder.

[0077] The dried powder was pressed into a target shape by a cold isostatic press with a pressing pressure of 80 MPa. The target was then placed in a sintering furnace under an oxygen atmosphere for sintering. The sintering temperature was set at 1300°C and the sintering time was 3 hours. The density of the sintered target was 98.5%. Finally, the target was slowly cooled to room temperature with a cooling rate controlled at 10°C / min.

[0078] The test results show that the target material has a high density (>95% theoretical density) and a resistivity of 2.2×10 -3 Ω·cm, suitable for thin film deposition and optoelectronic device manufacturing.

[0079] Embodiment 2:

[0080] Aluminum oxide powder and zinc oxide powder were mixed at a mass ratio of 90:10, and 1% calcium salt was added as a sintering aid. The other process steps were the same as those in Example 1.

[0081] The density of the sintered target is 98.2% and the conductivity is 2.0×10 -3 Ω·cm, with excellent optical and electrical properties, suitable for the field of optoelectronics.

[0082] Comparative Example:

[0083] Only aluminum oxide is used without zinc oxide, and other materials and process steps are the same as those in Example 1.

[0084] The density of the sintered target is 95.1%.

[0085] The principles and implementation methods of the present invention are described herein using specific examples, and the description of the above embodiments is only used to help understand the method and core ideas of the present invention. The above are only preferred implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention, which should be within the protection scope of the present invention.

Claims

1. A method for sintering a high-density indium-free target material doped with zinc oxide, characterized in that: The steps include: S1: After uniformly mixing aluminum oxide and zinc oxide powder in a mass ratio of (9-19):1, add sintering aid; S2: Add deionized water and dispersant, ball mill for 12 to 24 hours, filter and dry to obtain a primary powder; S3: sieving the primary powder to obtain a secondary powder with a particle size of ≤20 μm; S4: After the secondary powder is dried to completely remove moisture, it is pressed into a target shape using cold isostatic pressing or hot isostatic pressing; S5: Sinter in an oxygen atmosphere at 1200-1450°C for 2-4 hours and cool to room temperature after sintering.

2. The sintering method according to claim 1, characterized in that: Step S5 specifically includes the following sub-steps: S51, preheating: heating from room temperature to 1000°C at a heating rate of 5-10°C / min; S52, sintering: continue to raise the temperature to 1200-1450°C and maintain the temperature for 2-4h; S53, cooling: cooling to room temperature at a cooling rate of 10 to 15°C / min.

3. The sintering method according to claim 1, characterized in that: The sintering aid in step S1 includes calcium salt and / or borate, and the added amount thereof is 0.5% to 2% of the total mass of the aluminum oxide and zinc oxide powders.

4. The sintering method according to claim 1, characterized in that: The dispersant in step S2 includes citric acid or polyvinyl alcohol.

5. The sintering method according to claim 1, characterized in that: The pressing pressure in step S4 is 50 to 100 MPa.

6. The sintering method according to claim 3, characterized in that: The sintering aid is a surface-modified calcium salt-borate composite aid, and the preparation of the surface-modified calcium salt-borate composite aid comprises the following steps: Dissolving the silane coupling agent in a solvent to prepare a modifier solution with a concentration of 0.5% to 5%; Add calcium salt and borate to the modifier solution, stir or ultrasonicate for 1 to 3 hours, and then filter; The modified powder was washed with deionized water and dried at 60-100°C for 2-4h; The dried powder is sieved into a surface-modified calcium salt-borate composite additive with a particle size of ≤20 μm.

7. The sintering method according to claim 3, characterized in that: The sintering aid is an organic polymer-modified calcium salt-borate composite aid, and the preparation of the organic polymer-modified calcium salt-borate composite aid comprises the following steps: Dissolving an organic polymer in deionized water to prepare a polymer solution with a concentration of 2% to 10%; Add calcium salt and borate to the polymer solution, mix thoroughly with a magnetic stirrer or ultrasonic oscillator, and then filter; The product is obtained after drying at 60-100°C for 2-4 hours.

8. The sintering method according to claim 7, characterized in that: The organic polymer is polyvinyl alcohol, polyacrylonitrile or polyvinyl pyrrolidone.

9. The sintering method according to claim 2, characterized in that: The sintering method in step S5 is a gradual pressure sintering method, which specifically includes: During preheating, the pressure gradually increases from 0.1-0.5MPa to 1-3MPa; During sintering, the pressure gradually increases to 20-30 MPa; During cooling, the pressure gradually decreases to 1-3 MPa.

10. The sintering method according to claim 3, characterized in that: The sintering aid further comprises yttrium oxide and / or cerium oxide.